The devil colony ebook - Rollins, James (Sigma Force, 2011)
From James Rollins, the #1 New York Times bestselling author of the Sigma Force series, comes another electrifying combination of suspense, history, science, action, and ingenious speculation. Deep in the Rocky Mountains, a gruesome discovery—hundreds of mummified bodies—stir international attention and fervent controversy. Despite doubts about the bodies' origins, the local Native American Heritage Commission lays claim to the prehistoric remains, along with the strange artifacts found in the same cavern: gold plates inscribed with an unfathomable script. During a riot at the dig site, an anthropologist dies horribly: burned to ash in a fiery explosion in plain view of television cameras. All evidence points to a radical group of Native Americans, including one agitator, a teenage firebrand who escapes with a vital clue to the murder and calls on the one person who might help: her uncle, Painter Crowe, director of Sigma Force. To protect his niece and uncover the truth, Painter will ignite a war across the nation's most powerful intelligence agencies. Yet, an even greater threat looms as events in the Rocky Mountains have set in motion a frightening chain reaction, a geological meltdown that threatens the entire western half of the U.S. From the volcanic peaks of Iceland to the blistering deserts of the American Southwest, from the gold vaults of Fort Knox to the bubbling geysers of Yellowstone, Painter Crowe joins forces with Commander Gray Pierce to penetrate the shadowy heart of a dark cabal, one that has been manipulating American history since the founding of the thirteen colonies. But can he discover the truth—one that could topple governments—before it destroys all he holds dear?